Experience of European Clusters in Transsectoral Internationalization - Utkin, V. (Економічний вісник Донбасу, 2022)
This article discusses the importance of clusters in the modern economy as drivers of economic development, innovation, export, and better integration into international chains. The innovation cluster is a key element of the national (regional) innovation ecosystem, and the INNO Industry project aims to improve innovation development policies by involving clusters in Industry 4.0. The European Cluster Collaboration Platform is the main information tool for businesses in EU countries, offering opportunities for strengthening the European economy through the cooperation of industry cluster ecosystems. This platform allows any cluster initiative to be registered as a cluster organization, participant, or European cluster partnership, making it easy to find business partners for each country, region, sector or industrial ecosystem. Discusses the factors that affect the competitiveness of a cluster, which can be categorized as internal and external. The internal factors include material and technical support of production, management tactics and strategy, innovation, pricing policy, competitiveness of products, labor resources, employee motivation, and modern information technologies. On the other hand, external factors include market conditions, logistics infrastructure development, social, environmental, scientific, technical factors, and labor market situations. The abstract also highlights the stable or long-term objective factors such as geographic concentration, climatic conditions, availability of natural resources, regional and national characteristics that can influence the competitiveness but cannot increase it by themselves. Understanding and managing these factors can help improve the competitiveness of a cluster.